Prevalence and Obstetric Management Changes During the COVID-19 Pandemic in Peripartum SARS-CoV-2-Positive Women – an Analysis of the CRONOS Registry Data - Wowretzko, Feline; Büchel, Johanna; Tihon, Anastasia; Wöckel, Achim; Stefenelli, Ulrich; Pflanz, Mira; Longardt, Ann Carolin; Andresen, Kristin; Pecks, Ulrich (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
The analysis of CRONOS data for this article presents the infection prevalence among parturients and subsequent changes in obstetric management over time in Germany. 2,184 women with peripartum SARS-CoV-2 infection (<14d before birth) were included. Monthly period prevalence was calculated using the number of affected women on the CRONOS registry relative to total monthly births in each hospital from March 2020 to May 2022 and compared to RKI data. Trends related to changes in obstetric management were calculated based on severity of illness. By June 2021, the obstetric population shows a discretely higher infection prevalence compared to the general population, falling below the RKI reported prevalence by October 2021. The overall rate of iatrogenic deliveries remains unchanged over time (p-value for trend=0.779). During wave 1 to 4, deliveries due to SARS-CoV-2 infection rose among moderately to severely ill women (p-value for trend 0.0000) and was increased compared to moderately ill women (p=0.001). We showed that comprehensive screening provides timely information on infection prevalence. Recruitment fatigue caused by higher clinician workload due to increased admissions and more cases with severe illness probably caused reduced prevalence reporting. Changes in obstetric management were related to COVID-19 symptom severity. A comprehensive national perinatal registry is needed to examine other areas of perinatal care in Germany.
Keywords: CRONOS; SARS-CoV-2; obstetric outcome; perinatal outcome; COVID-19